الممارسات الخاطئة للأمهات أثناء العناية بحديثي الولادة - Ghadban, Rajaa Saleh (Latakia University Journal -Medical Sciences Series, 2019)
الممارسات الخاطئة للأمهات أثناء العناية بحديثي الولادة رجاء صالح غضبان تعد العناية بحديثي الولادة من المسؤوليات الأساسية للأمهات إذ يمكن من خلالها الحد من نسبة الأمراض والوفيات خلال الشهر الأول من الحياة . تقوم العديد من الأمهات بممارسات خاطئة أثناء العناية بولدانها وذلك بناءً على تجارب الأقارب والآخرين مما قد يسبب مضاعفات قد تهدد صحة وحياة الوليد, لذلك من الضروري أن تمتلك الأمهات الممارسات الصحيحة الخاصة بالعناية بولدانها استناداً على قاعدة علمية وليس على عادات وتقاليد, لذلك هدفت هذه الدراسة إلى تقييم الممارسات الخاطئة للأمهات أثناء العناية بحديثي الولادة. أجريت الدراسة على عينة قوامها 100 أم تم اختيارهن بطريقة العينة العشوائية البسيطة من مستشفى التوليد والأطفال الوطني باللاذقية , وجمعت البيانات باستخدام استبيان مطور لهذا الغرض. أظهرت نتائج الدراسة الحالية أن غالبية الأمهات لديهن ممارسات خاطئة فيما يتعلق بقيامهن بتمليح الوليد عند أول حمام له ووضع وسادة تحت رأسه ولف رباط حول جسمه وهزه لكي ينام. وقد أوصت الدراسة بضرورة إجراء برامج تثقيفية بهدف تحسين مستوى الوعي والممارسات لدى الأمهات اللاتي يعتنين بحديثي الولادة و تفعيل دور الممرضات من خلال دورهن التثقيفي الذي يمكن أن تقدمه للأمهات وكذلك إجراء مزيد من الدراسات لتحديد العوامل التي تؤثر على ممارسات ومعتقدات الأمهات أثناء رعاية حديثي الولادة. Neonatal care is one of the basic responsibilities of mothers. it is possible to reduce the incidence of diseases and deaths during the first month of life. Depending on the experiences of relatives and others, many of mothers do wrong practices during caring their neonates, which may cause complications that may threaten the health and life of the newborn. It is therefore necessary for mothers to have the right practices to care for their neonates based on a scientific basis rather than habits and traditions ,so this study aimed to assessment of mothers, practices during neonatal care , this study applied on a sample consists of 100 mothers were randomly by using simple random sampling selected from the maternity and national children hospital in Lattakia , data were collected using a questionnaire developed for this purpose. The results of the current study showed that the majority of mothers had malpractices such as salting the newborn, placing a pillow under the head of the newborn and putting a strap around his body and shaking to sleep. The study recommended that educational programs should be carried out to improve the awareness and practices of mothers, caring for newborns, activate the role of nurses through their educational role, and further studies to identify factors affecting the practices and beliefs of mothers during neonatal care.